Board game as an educational media for dengue prevention knowledge for school-aged children - Amelia, Vivi Leona; Setiawan, Agus; Sukihananto (Enfermería Global, 2019)
Indonesia is one of the endemic countries for dengue fever, and for the incidents are increasing year by year. Children are the risk population to dengue incidents than the others age groups. Part of the dengue prevention is increasing the knowledge, and also the children’s knowledge. The use of the game is the enjoyable way for learning in children. Aim: The aim of the study was to know children's basic knowledge about dengue prevention and develop an educational media for children. This study uses a quasi-experimental design with pre and post-test and using a control group. Method: The participants are a school-aged children between the ages of 10-12 years old with total 92 participants who were divided into intervention group and control group. Results: The results showed that there are a significantly increasing score at children basic knowledge at intervention group about dengue fever sign and symptom (p=0,001); prevention strategy based on Indonesia Health Ministry guidelines (p=0,001); chemistry agent (p=0,000); biology agent (p=0,000); self-protection (p=0,001); and immune system (p=0,001). There are difference knowledge between intervention and control groups (p=0,000). Conclusion: The conclusion of the study is board game can be designed to be an educational media to give a health education about dengue prevention strategy to the children.